Kidney transplantation from brain-dead donors in Nepal: Report of first six cases. (September 2022) - Shrestha, Pukar Chandra; Bhandari, Tika Ram; Devbhandari, Mohan; Verma, Rakesh Kumar; Shrestha, Kalpana Kumari
Abstract: Introduction: and importance: Kidney transplantation is one of the best treatment options for patients with end-stage renal disease. More than 90% of patients awaiting renal transplantation die without getting the kidney for transplantation. Brain dead donor kidney transplantation can bridge this gap proficiently. We aim to report details of the first six patients who had undergone brain-dead donor kidney transplantation in the history of transplantation in Nepal. Case presentation: We conducted a descriptive analysis of clinical data of six adult recipients with kidney transplantation from three brain-dead donors. We described postoperative complications, length of stay, graft function which was documented with serum creatinine, acute rejection episode, delayed graft function, and patient/graft survival of recipient. Recipients were between 15 and 56 years old. Three patients experienced delayed graft function. Urinary tract infection was observed in two patients, both of whom were treated with antibiotics. One patient had acute graft rejection. None of our patients required reoperation. Length of hospital stay ranged from 9 to 32 days. The postoperative graft function was 100% in all patients. There was no graft loss, and no death was observed during follow-up. Clinical discussion: Following the initiation of the brain-dead donor transplantation program, a lot of work needs to be done to make it a regular practice. Thus, this program needs support from all sections of society and government. This can be the only solution to decrease the huge gap between the supply and demand of organs in Nepal. Conclusion: This case reports indeed revealed impressive success in initiating a brain-dead donor kidney transplantation program in a developing country that in terms of quality, meets comprehensive standard with acceptable graft function and patient/graft survival in under limited resources healthcare setting. Highlights: Kidney transplantation is one of the best treatment options for patients with end-stage renal disease. More than 90% of patients awaiting renal transplantation die without getting the kidney for tranplantation. Brain dead donor kidney transplantation can bridge this gap proficiently. We reported first six patients with brain dead donor kidney transplantation in the history of transplantation in Nepal.